UPAYA MENINGKATKAN KETERAMPILAN MEMBACA AKSARA JAWA MELALUI MEDIA AUDIO VISUAL PADA SISWA KELAS IV SD NEGERI 2 GADINGHARJO SANDEN BANTUL - Mila Tiyarasari; Y. B. Maridja (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Abstract: This study aimed to describe (1) students’ activities in the teaching of reading skills of Java letters through audio visual media and (2) the improvement of reading skills of Java letters through audio visual media among the fourth grade students of SD Negeri 2 Gadingharjo. The type of this study was classroom action research in the teaching of reading skills of Java letters. The subject of the research was the fourth grade students of SD Negeri 2 Gdaingharjo Sanden Bantul consisted of 39 students. The object of the research was reading skills of Java letters. Data collecting methods used test, observation, and documentation. This research used validity by using expert judgment. This study shows that (1) the use of audio visual could improve the students’ activities among the fourth grade students of SD Negeri 2 Gadingharjo. The students’ activities in pre cycle was 38.97%, cycle I was 67.69%, and cycle II was 89.74%. (2) The use of audio visual media could improve reading skill of Java letters among the fourth grade students of SD Negeri 2 Gadingharjo. The students’ reading skills show that there was an improvement from pre cycle until cycle II. The percentage of complete learning from pre cycle was 35.90% became 61.54% in cycle I and more improved in cycle II became 87.18%. It could be concluded that the use of audio visual media could improve learning activities and reading skills of Java letters.